2013
DOI: 10.1371/journal.pone.0077847
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Nuclear-Encoded Genes of Oxidative Metabolism in Dialyzed Chronic Kidney Disease Patients

Abstract: BackgroundMitochondria, essential eukaryotic cells organelles defined as the “powerhouse of the cell” because of their ability to produce the vast majority of energy necessary for cellular metabolism, may have a primary role in the oxidative stress-related intracellular machinery associated to chronic kidney disease (CKD).MethodsTo better assess this research assumption, we decided to study the key factors regulating mitochondrial oxidative metabolism in CKD patients in peritoneal dialysis (PD, n = 15) using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 36 publications
2
52
0
Order By: Relevance
“…Consequently inflammation-induced impairment of Nrf2 activation contributes to its depressed expression, as seen in the present study. It is of interest that, in a recent study, Zaza et al [39] found a significant increase in Nrf2 and SOD2 expressions in the PBMC of CKD patients maintained on peritoneal dialysis, contrasting the results found in hemodialysis patients. This may reflect the higher burden of inflammation in hemodialysis patients caused by intermittent blood exposure to the extracorporeal circuit and the dramatic rise and fall in body fluid volume during the inter-and intra-dialytic intervals.…”
mentioning
confidence: 89%
“…Consequently inflammation-induced impairment of Nrf2 activation contributes to its depressed expression, as seen in the present study. It is of interest that, in a recent study, Zaza et al [39] found a significant increase in Nrf2 and SOD2 expressions in the PBMC of CKD patients maintained on peritoneal dialysis, contrasting the results found in hemodialysis patients. This may reflect the higher burden of inflammation in hemodialysis patients caused by intermittent blood exposure to the extracorporeal circuit and the dramatic rise and fall in body fluid volume during the inter-and intra-dialytic intervals.…”
mentioning
confidence: 89%
“…[23][24][25] A large number of studies have shown that mitochondrial dysfunction plays an important role in the progression of renal disease including renal tubular injury, chronic kidney disease, and acute renal failure, which can lead to renal disease aggravation and progression. [26][27][28] More and more evidences suggested that the damage of mitochondrial morphological and function plays an important role in the development of DN. 29,30 Malik et al 31 found that mitochondrial DNA copy number of peripheral blood in patients with DN is significantly higher than the DM group without nephropathy, which prompted that mitochondrion plays a key role in DN, namely, mitochondrial fission is increasing under HG.…”
Section: Introductionmentioning
confidence: 99%
“…16,[19][20][21][22] Recently increasing evidences showed mitochondrial dysfunction in a broad spectrum of pathogenesis of renal diseases. Moreover renal diseases patients exhibited an impaired mitochondrial respiratory system.…”
mentioning
confidence: 99%
“…Tubular epithelial cell damage causes from apoptosis/necrosis and epithelial-mesenchymal transition, additionally, endothelial dysfunction causes from apoptosis/necrosis and endothelial-mesenchymal transition. 18,19,[21][22][23][24][25][26] Studies have shown significantly increased ROS production, up-regulation of TGF-β expressions, high glucose levels, proteinuria, uremic toxins, ischemia/hypoxia, and activation of RAAS in peripheral blood mononuclear cells of patients, thereby demonstrating the close association between mitochondrial dysfunction and renal diseases progression. 21,25,27,28 Recently, a number of studies have revealed that regulation of co-activators can physiologically signal to specific transcription factor targets.…”
mentioning
confidence: 99%
See 1 more Smart Citation